A multifunctional metal–organic framework based tumor targeting drug delivery system for cancer therapy. Issue 38 (15th September 2015) - Wang, Xiao-Gang; Dong, Zhi-Yue; Cheng, Hong; Wan, Shuang-Shuang; Chen, Wei-Hai; Zou, Mei-Zhen; Huo, Jia-Wei; Deng, He-Xiang; Zhang, Xian-Zheng
Abstract : A tumor targeting dual stimuli-responsive drug delivery system was developed by one-pot, and organic solvent-free "green" post-synthetic surface modification of the nanoscale metal–organic framework MIL-101. Abstract : Drug delivery systems (DDSs) with biocompatibility and precise drug delivery are eagerly needed to overcome the paradox in chemotherapy that high drug doses are required to compensate for the poor biodistribution of drugs with frequent dose-related side effects. In this work, we reported a metal–organic framework (MOF) based tumor targeting DDS developed by a one-pot, and organic solvent-free "green" post-synthetic surface modification procedure, starting from the nanoscale MOF MIL-101. Owing to the multifunctional surface coating, premature drug release from this DDS was prevented. Due to the pH responsive benzoic imine bond and the redox responsive disulfide bond at the modified surface, this DDS exhibited tumor acid environment enhanced cellular uptake and intracellular reducing environment triggered drug release. In vitro and in vivo results showed that DOX loaded into this DDS exhibited effective cancer cell inhibition with much reduced side effects.